An ecological perspective on minority and majority language and literacy communities in the Americas - Reyes, Iliana (Colombian Applied Linguistics Journal, 2009)
In this paper I discuss current sociolinguistic situations in linguistically diverse communities in the Americas, thereby contributing toward the development of a theoretical model that focuses on the ecology of emergent bilingualism and biliteracy for both language-minority and language-majority children. I analyze different examples in which children’s participation during family literacy events mediate the learning of the second language and their construction of meaning from print they encounter in their bilingual surroundings. The review points to the potential to develop bilingualism and biliteracy that might exist within each child’s immediate environment and are enhanced when community members (e.g., parents, peers, schoolteachers, neighbors) provide direct scaffolding during child-adult interactions. The studies are discussed within an eco-sociocultural framework making pedagogical connections and recommendation to the optimal development of bilingualism and biliteracy.